Direct Marketing Strategy Produk Sabun Organik Untuk Meningkatkan Penjualan Di kelurahan Tumatangtang Satu - Gratciany Rumondor; Willem G. Pomantow; Wingston M. J. Longdong; Nancy H. J. Mandey (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
The Covid-19 pandemic that occurred in Indonesia caused problems such as layoffs. One of the impacts was the reduced welfare of families because female workers no longer worked. In an effort to improve family economy, the Family Income Improvement Effort (UP2K) program was established to enhance the role of PKK (Family Welfare Movement) members in helping their families prosper through the development of micro-enterprises and fostering the entrepreneurial spirit of each PKK member. This study aims to increase the use of effective direct marketing strategies through social media in promoting organic soap products to consumers and increasing sales. The method used in this research is qualitative, describing data obtained through interviews. The results of this study show that the organic soap product has been marketed by placing it in souvenir shops and through Facebook social media. Many people still do not know the benefits of organic soap, so sales have not increased. The conclusion of this research is that the marketing strategy used, namely Direct Marketing, gives good results in increasing knowledge about the benefits of organic soap, increasing consumer purchase interest, and expanding market share.